Engaging the youth: co-designing health promotion messages. (30th September 2020) - Finlay, S
Abstract: We were all young once, right? Moreover, many of us still feel young despite our birth certificate suggesting otherwise. Does that mean we understand what health promotion messages are going to resonate with young people today? Does it mean we know which platforms messages for young people should be used? The short answer is no. This is particularly true for marginalised communities whose needs are often very different and therefore require tailored communication. Marginalised communities such as Indigenous people, the LGBTQI community, migrant populations and refugees. Youth is a perfect time to communicate prevention, sexual and reproductive health and other health promotion messages. Young people are our future leaders. As health professionals, we want to make sure they transition to adulthood as healthy in mind and body as we can. Part of that is developing health promotion messages which reach with young people. However, too frequently, messages are not tailored for young people; therefore, not equipping them with the knowledge and skill to make healthy choices. To ensure that as health professionals that we are maximising our impact with young people, we need to co-design health promotion messages with them. Like with many Indigenous people in colonised countries, half of the Aboriginal and Torres Strait Islander population, Australia's Indigenous people are under the age of 30. Young Australian Indigenous people's health and wellbeing needs are distinctive because of the uniqueness of their culture as well as the historical, political and social context (Azzopardi 2017). To ensure that health promotion effectively reaches its target audience, a co-design methodology is often employed with Aboriginal and Torres Strait Islander people. This presentation will detail the development of co-designed quit smoking and suicide prevention health promotion campaigns to demonstrate their effectiveness. A method that can be applied with other young people for maximum impact.